Agrobacterium-mediated transformation of an elite indica rice for insect resistance - Ignacimuthu, S.; Arockiasamy, S.
In India, rice occupies the largest area among all crops and accounts for as much as 21
Keywords: AGROBACTERIUM; ALPHA AMYLASE INHIBITOR; RICE; SITOPHILUS ORYZAE